Exhibition Review Essays. Issue 1 (1st July 2021) - Brulon Soares, Bruno; Coombes, Jennifer; Wallace-Buckland, Ailish; Tawhiao, Hollie
Abstract : The Museum of Removals in Vila Autódromo, Rio de Janeiro by Bruno Brulon Soares Different Histories: A Story of Three Exhibitions in Canberra by Jennifer Coombes National Treasures: Airing New Zealand's History on the Small Screen by Ailish Wallace-Buckland E Hina e! E Hine e! Mana Waahine Maaori/Maoli of Past, Present and Future by Hollie Tawhiao